PENGARUH KEPEMIMPINAN DAN LINGKUNGAN KERJA FISIK TERHADAP KINERJA KARYAWAN PADA PT. BEARINDO ELOK SEJAHTERA TANGERANG SELATAN - Helmi Yansyah Putra; Lidya Pricilla (Jurnal Menara, 2026)
This study aims to determine the positive and significant influence of leadership and physical work environment on employee performance at PT. Bearindo Elok Sejahtera, South Tangerang, both partially and simultaneously. The study uses a sample of 80 respondents and applies a quantitative method based on a Likert scale. Various tests were conducted including Descriptive Analysis, Instrument Testing, Classical Assumption Tests, Quantitative Analysis, and Hypothesis Testing. Based on the results of simple linear regression, the leadership variable has the equation Y = 21.770 + 0.528X₁, while the physical work environment variable has the equation Y = 21.102 + 0.547X₂. The multiple regression calculation for leadership (X₁) and physical work environment (X₂) resulted in the equation Y = 19.232 + 0.245X₁ + 0.358X₂. The t-test for leadership yielded a t-count > t-table (7.257 > 1.991) with a significance value of 0.00 < 0.05. Thus, Ha₁ is accepted and Ho₁ is rejected, indicating that leadership has a significant effect on employee performance. The t-test for the physical work environment showed a t-count > t-table (7.872 > 1.991) with a significance value of 0.00 < 0.05, meaning Ha₂ is accepted and Ho₂ is rejected—indicating a significant influence of the physical work environment on performance. The F-test shows F-count > F-table (34.981 > 3.115) with a significance of 0.00 < 0.05, meaning Ha₃ is accepted and Ho₃ is rejected, confirming that leadership and physical work environment have a simultaneous influence on employee performance.